Stability Study of Pashanbhedadi Churna Used in Treatment of Ashmari (Renal Calculi): with Respect to Baseline Microbial Diagnostic Modalities (International Journal of Ayurveda and Pharma Research, 2023)
Ashmari (Renal Calculi) is most common disease of urinary system. Ashmari or calculus looks like small gravels/stones hence they are termed as Ashmari. For the treatment of Ashmari Pashanbhedadi Churna was taken as a trial drug. As Pashanbhedadi Churna was trial drug it was necessary to check the stability. Stability of the drug is the time period from the drug production until the time it is intended to be consumed. So, present study was carried out to know the stability of Pashanbhedadi Churna and to check microbial contamination in the Pashanbhedadi Churna at different time interval. Pashanbhedadi Churna was stored in plastic bag. Microbial study of the drug was done at different climatic conditions, humidity and temperature set ups with regular intervals for a period of 11months to analyse mycological and bacteriological findings by wet mount preparation and Gram stain test respectively. Though in different climate, temperature and humidity conditions, at the end of microbial study, Churna has shown absence of microbes for approx.11 months of preparation of drug. So, it is showed that drug is stable in minimum 32°C temperature to maximum 38°C and minimum humidity 23% to maximum 74% humidity. That means stability duration of drug after preparation is approx. 11 months which showed that drug was in a standard condition. Hence it is concluded that stability test of Pashanbhedadi Churna with respect to microbiological findings was negative at room temperature, warm and cold, dry and humid conditions.